Outage performance analysis of NOMA under fading channels in presence of imperfect SIC - Nhat-Tien Nguyen; Hong-Nhu Nguyen; Miroslav Voznak; Le-Chi Bao; Nhan Duc Nguyen (Institute of Advanced Engineering and Science, 2022)
The introduction of 5th and 6th-generation wireless networks has elevated the demand for huge device connectivity, spectral efficacy, and improved signal quality. The non-orthogonal multiple access technique (NOMA) has been demonstrated to be a candidate to address these requirements. NOMA can assist many users using the same resource block by varying the assigned power levels fairness to the users. To perform this, the NOMA technique superimposes the signals from both the users and transmits them to the receiver. On the receiver side, it performs successive interference cancellation (SIC) techniques to separate the respective signals. Meanwhile, the fading channels also play a major role in deciding the quality of the signal that is being transmitted. In our paper, a NOMA system is considered in presence of two users having fading channels. The closed-form expressions are derived for outage probability and throughput of the system in presence of perfect SIC and imperfect SIC. The expressions are numerically analyzed by varying various parameters such as fading channels, power level coefficients, and the number of antennas at the receivers. The obtained results demonstrate that each parameter plays a major role in enhancing the quality of each user's signal and the outage performance of the system.